Information Technology-Based Learning to Increase Secondary School Students’ Learning Interest - Raudya Setya Wismoko Putri; Saliman Saliman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the efforts of blended learning in increasing interest in learning Social Sciences in a secondary school. This study uses the Kemmis McTaggart action research model. The research was carried out throughout two cycles. Each cycle includes four levels, namely planning, implementation of activities, supervision, and contemplation consisting of 3 meetings per cycle. The data collection techniques used were observation forms, field notes, documents, questionnaires, and tests. A descriptive analysis of qualitative data was used to analyze the data. The results of the study prove that the use of blended learning in this school can increase interest in learning social studies using the blended learning phase between traditional courses and virtual/virtual courses. In-class learning and teacher-supervised mixed learning, and virtual classroom learning require students to study independently without teacher supervision. Using this type of learning will increase students' interest in learning from Cycle I to Cycle II. The average value of the first cycle is 63.5%, and the average value of the second cycle is 81%. Various aspects also experienced development. From cycle I to cycle II the average aspect of student attention experienced an escalation of 20%. From Cycle I to Cycle II, thirst increased by an average of 17%. Activity increased by an average of 19%. Cycle I and Cycle II curiosity increased by 21%. Enjoyment period I to period II increased by 17%. Confidence increased 16% from Cycle I to Cycle II.